Proceedings 15th IEEE Computer Security Foundations Workshop. CSFW-15
DOI: 10.1109/csfw.2002.1021821
|View full text |Cite
|
Sign up to set email alerts
|

A privacy policy model for enterprises

Abstract: Privacy is an increasing concern in the marketplace. Although

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 12 publications
(30 reference statements)
0
89
0
Order By: Relevance
“…To address this limitation, many logics and languages have been proposed for specifying privacy policies. Some examples are P3P [48,49], EPAL [50,51], Privacy APIs [52], LPU [53,54], past-only fragment of first-order temporal logic (FOTL) [10,11], predLTL [55], pLogic [56], PrivacyLFP [12], MFOTL [5][6][7], the guarded fragment of first-order logic with explicit time [4], and P-RBAC [57]. Our policy language, GMP, is more expressive than many existing policy languages such as LPU [53,54], P3P [48,49], EPAL [50,51], and P-RBAC [57].…”
Section: Related Workmentioning
confidence: 99%
“…To address this limitation, many logics and languages have been proposed for specifying privacy policies. Some examples are P3P [48,49], EPAL [50,51], Privacy APIs [52], LPU [53,54], past-only fragment of first-order temporal logic (FOTL) [10,11], predLTL [55], pLogic [56], PrivacyLFP [12], MFOTL [5][6][7], the guarded fragment of first-order logic with explicit time [4], and P-RBAC [57]. Our policy language, GMP, is more expressive than many existing policy languages such as LPU [53,54], P3P [48,49], EPAL [50,51], and P-RBAC [57].…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, the same information can be expressed differently or require a different level of granularity. For instance, the retention period expressed as a data element in P3P is represented as an obligation in E-P3P [72].…”
Section: Privacy Alignment and Compliance Discussionmentioning
confidence: 99%
“…These three elements, however, are insufficient to specify data protection policies [52,29]. In addition to the above three basic authorization elements (subjects, objects, and actions), Karjoth et al [72] identified other three elements that shall occur in data protection policies, namely purpose, condition, and obligation. Based on this observation, a number of languages and models tailored to specify and enforce data protection policies were proposed [58,13,14,26,44].…”
Section: Privacy-aware Access Controlmentioning
confidence: 99%
“…It provides a privacy permission assignment language using purpose, condition, and obligation. Another privacy policy model for enterprises is described in [8]. These systems concentrate only on privacy preserving without a focus on enhancing sharing among collaborators.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Collaborative access control and privacy for Web-based social networks is described in [7]. A privacy policy model for enterprises is described in [8]. These systems concentrate only on privacy preserving without a focus on enhanced sharing among collaborating users.…”
Section: Introductionmentioning
confidence: 99%